Anthropometric characteristics of professional football players in relation to the playing position and their significance for success in the game - Joksimovic, M.; Skrypchenko, I.; Yarymbash, K.; Fulurija, D.; Nasrolahi, S.; Pantovic, M. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2019)
Background: Football is a game in which anthropometric characteristics are important factors for specific player positions, where morphological characteristics differ in relation to the competitive level and the position in the game. Body composition is an important indicator of the physical fitness and general health of athletes so today its often discussed in scientific literature. The aim of the research was to determine the differences in the anthropometric characteristics of the professional football players in relation to the player's position and to determine their importance in the game. Material: Twenty-nine male football players of the national team of Serbia participated in the research, in which the body height, weight and Body mass index were measured. Results: The results of the study indicate that statistically significant differences in body height and body weight were recorded between goalkeepers and midfielders (p <0.01) and goalkeepers and attackers (p <0.05) in favor of goalkeepers, while no statistically significant differences were recorded in the Body Mass Index. The lowest height, weight and BMI were recorded in the midfielders. Conclusions: Based on the results of the research it can be concluded that the morphological characteristics have a vital role in determining the success of athletes. Football coaches can use the results of this study as a means to better understand and interpret anthropometric characteristics and their importance in relation to the gaming position. The acquaintance of noticed differences could improve the training process as well as the selection at the early age.